Afatinib treatment response in advanced lung adenocarcinomas harboring uncommon mutations. Issue 21 (21st September 2021) - Li, Teng; Wang, Shouzheng; Ying, Jianming; Wang, Yan; Hu, Xingsheng; Hao, Xuezhi; Xu, Ziyi; Xing, Puyuan; Li, Junling
Abstract: Background: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have improved the prognosis of mutant lung cancer; however, the clinical application value of TKIs for nonclassical EGFR mutation is unclear, especially for patients with rare uncommon mutations. Methods: A retrospective study based on electronic medical records was conducted to collect data on the effectiveness of afatinib in patients with stage IIIB/IV lung adenocarcinoma (LUAD) bearing uncommon mutations between January 2017 and January 2021. Results: Forty‐two patients with uncommon mutations treated with afatinib were enrolled. The objective response rate (ORR) was 50.0% (10 of 20 patients). The median time to treatment failure (TTF) was 11.7 months (95% confidence interval = 8.5–18.3 months). Of the 42 patients, the median TTF was 15.0, 11.7, and 16.6 months in patients with Gly719Xaa (G719X), Ser768Ile (S768I), and Leu861Gln (L861Q) mutations, respectively. In patients with the rare uncommon mutation, the median TTF was 10.0 months, and the ORR was 50.0%. Afatinib demonstrated clinical activity across a set type of specific rare uncommon mutations, including EGFR L747P, A767_V769dup, and L833V/H835L, with a case having a TTF of more than 1 year. Molecular profiling reports of 16 afatinib‐resistant biopsy samples were available, and the secondary T790M mutation was detected in one patient with L833V/H835L mutation and one harboring S768I/L858R mutation. Conclusions: Our findings suggested that afatinib is effective in patients with uncommon mutations. Mechanisms of afatinib resistance vary and need further investigation. Abstract : This study was designed to evaluate the responses to afatinib treatment of patients with G719X, L861Q, S768I, and other rare uncommon mutations, as well as and determine the clinical demographics and underlying mechanisms of resistance. Our findings suggest that afatinib is effective in patients with uncommon EGFR mutations. Detailed reports for specific rare uncommon mutations provide reliable evidence for clinical practice.